The concept of death among young children - Nuada, Donna Ponce; Juadiong, Lillian Leynes (2005)
This study explored the concept of death of forty-two, three, five, and seven year old children and investigation of four components of death- universality, irreversibility, nonfunctionality and causality. Universality is the understanding that all living things eventually will die and that no one can escape death. Irreversibility is the understanding that death is cannot be reversed by magic, medicine, food and water of other means. Nonfunctionality is the understanding that death ends all movement, feeling, sensation, thought and other abilities. Causality is the understanding that there are physical/biological reasons why death occurs. The study aimed primarily to describe the understanding of death in terms of the four components and to establish whether the age and religion of the child can be a factor related to the understanding of death. Due to the sensitivity and the nature of the young children who participated in the study two kinds of data gathering instruments were developed. The researcher developed an original data-gathering tool to address the nature of young children who participated in the study. The tool was content validated by Early Childhood Specialists. Complementary to the open-ended questionnaire the children were read a story to situate the event. Data collection was divided into two phases. The first phase involved the giving out of preliminary letters to the chairman, principals, and faculty in the charged center, to ask permission to allow the researcher to conduct the study. In the second phase, children who participated were interviewed using the open-ended questionnaire, which is composed of seven questions in Filipino regarding death concept. After which the children were asked to draw what death means to support the interview. Both questionnaire and quantitative methods were employed after the results from the interview was collected and organized. After the response were categorized, frequencies and percentages of the responses were determined. To determine if age and religion are related to child's understanding of death in terms of the four components, Pearson Product Moment Coefficient of Correlation was used. Other statistical tools employed were T-test, Analysis of Variance and Scheffe's Test of Comparison. Results showed that the three year olds do not have a concept of death in terms of the three components only-irreversibility, nonfunctionality and causality and do not grasp the universality component. The seven year olds clearly understand death in terms of four components: universality, irreversibility, nonfunctionality and causality. Based on the results of the Pearson Product Moments Correlation of Coefficient, the hypothesis that there is no relationship between age and child's understanding of death in terms of the four components is rejected. This implied that age as a factor influenced children's concept of death. results of the Pearson also revealed that religion has no significant relationship on child's understanding of death in terms of the four components. Parents and teachers play a vital role in informing what death is to young children. Simple, clear and honest answers are what they need to fully understand what death is. Further studies that will deepen the understanding of death of young children and that will investigate other factors affecting child's concept of death are recommended.
"May 2005."
Thesis (M. Family Life and Child Development)--University of the Philippines, Diliman.
Keywords: Children and death -- Philippines -- Manila Metropolitan Area